A Joint MMSE Scheme for Multiuser AF Relaying Systems Under Power Constraints - Chang, Kyungsik; Lim, Jaesung; Lee, Kanghee (IEEE Systems Journal, 2018)
This letter studies a minimum mean square error (MMSE) relay strategy for multiuser amplify-and-forward relaying system consisting of M source-destination pairs between N relays with only a single antenna per node. We design jointly and explicitly optimal diagonal relay amplifying and destination decoder matrices under relay transmit power constraints. By adopting the derived optimal relay amplifying matrix, the MMSE cost function (CF) behavior is analytically and numerically investigated. In addition, it is analytically and numerically shown that the MMSE CF values are always less than M, regardless of N if M ≥ N. And an efficient iterative algorithm with a small number of iterations is proposed to solve the jointly desired optimization problem. Finally, simulation results show that the proposed scheme outperforms the existing ones.
Keywords: Amplify-and-forward relaying; Iterative algorithm; Minimum mean square errors (MMSE); Number of iterations; Optimization problems; Power constraints; Relay strategies; Relaying systems; Amplify-and-forward (AF); minimum mean square error; power constraint